Improvement of the operation characteristics of the precipitated coatings on the steel 12x18h10t by means of the method of thermodiffusion processing - Лобурак, В.Я.; Лук’янюк, М.В. (Problems of Tribology, 2014)
The research conducted tested heat-tolerance and wearproofness by spraying arc-plasma at a galvanically and electrolytically besieged composition that covered steal 12X18H10T after thermo-chemical treatment. The results showed that TCT, in all cases, promotes the operating properties of the coverages, and is an effective application that is simpler and more effective in this technological process.